Measurements of wire + arc additive manufacturing layer heights during arc operation using coherent range-resolved interferometry (CO-RRI) - Kissinger, Thomas; Gomis, B.; Ding, Jialuo; Williams, Stewart; Tatam, Ralph P. (EUSPEN, 2019)
Wire + arc additive manufacture (WAAM)promises high build rates and is well-suited to the manufacture of large structures.In-process measurements of layer height are critical for WAAM process control but are difficult to achieve due to the presence of bright arc light. In this paper, a novel coherent range-resolved interferometric (CO-RRI) technique is successfully applied to the measurement of layer heights during arc operation in a first step towards gaining full in-process control of deposition layer heights.
Keywords: In-process measurements; Additive manufacturing; Range-resolved interferometry,; Coherent measurements; Optical instrumentation